1988
DOI: 10.1007/bf02549568
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic lithotripsy of bladder stones

Abstract: In the second half of 1985, 15 patients with 25 bladder stones were treated with Lutzeyer's Ultrasonic Lithotriptor. Of the patients 13 underwent additional operations, mostly transurethral resection of the prostate. The average duration of lithotripsy was 30.5 minutes. Some difficulties were experienced especially when drilling hard stones and as a complication late urethral bleeding occurred in one patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Both require anaesthesia and hospitalisation and are associated with some morbidity. Larger stones require the help of the ultrasound or electrohydraulic lithotriptor (Cetin et al, 1988 ;Yip and Tin, 1988;Zhaowu et al, 1988). While using these ancillary aids it is possible, as a result of friction, to erode the mucosa of the bladder or perforate the bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both require anaesthesia and hospitalisation and are associated with some morbidity. Larger stones require the help of the ultrasound or electrohydraulic lithotriptor (Cetin et al, 1988 ;Yip and Tin, 1988;Zhaowu et al, 1988). While using these ancillary aids it is possible, as a result of friction, to erode the mucosa of the bladder or perforate the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are also time-consuming. Cetin et al (1988) reported urethral bleeding as a result of lithotresis of hard stones.…”
Section: Discussionmentioning
confidence: 99%